Physical activity and lifestyle modifications in the treatment of neurodegenerative diseases - Santiago, Jose A.; Potashkin, Judith A. (Frontiers in Aging Neuroscience, 2023)
Neurodegenerative diseases have reached alarming numbers in the past decade. Unfortunately, clinical trials testing potential therapeutics have proven futile. In the absence of disease-modifying therapies, physical activity has emerged as the single most accessible lifestyle modification with the potential to fight off cognitive decline and neurodegeneration. Here we discuss findings from epidemiological, clinical, and molecular studies investigating the potential of lifestyle modifications in promoting brain health. We propose an evidence-based multidomain approach that includes physical activity, diet, cognitive training, and sleep hygiene to treat and prevent neurodegenerative diseases.